2015
DOI: 10.1007/s12088-015-0516-x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activities of Silver Nanoparticles Synthesized by Using Water Extract of Arnicae anthodium

Abstract: Green synthesis of nanoparticles has gained significant importance in recent years and has become the one of the most preferred methods. Also, green synthesis of nanoparticles is valuable branch of nanotechnology. Plant extracts are eco-friendly and can be an economic option for synthesis of nanoparticles. This study presents method the synthesis of silver nanoparticles using water extract of Arnicae anthodium. Formation of silver nanoparticles was confirmed by UV-visble spectroscopy, Fourier transform infrare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…Bands displacement can indicate interaction between the components of PVA and pomegranate, that is, the displacement of PVA bands around (1700–1750 cm −1 ) with the addition of dextran to PVA can be considered a hydrogen bonding formation between components . The PVA‐arnica samples presented, basically, the PVA bands, although some arnica bands, that is, bands at 1639, 1086, and 1045 cm −1 could be overlapped to PVA bands, Table . No new bands were found in PVA–pomegranate samples or in PVA‐arnica samples, indicating no chemical interactions .…”
Section: Resultsmentioning
confidence: 96%
“…Bands displacement can indicate interaction between the components of PVA and pomegranate, that is, the displacement of PVA bands around (1700–1750 cm −1 ) with the addition of dextran to PVA can be considered a hydrogen bonding formation between components . The PVA‐arnica samples presented, basically, the PVA bands, although some arnica bands, that is, bands at 1639, 1086, and 1045 cm −1 could be overlapped to PVA bands, Table . No new bands were found in PVA–pomegranate samples or in PVA‐arnica samples, indicating no chemical interactions .…”
Section: Resultsmentioning
confidence: 96%
“…The band observed at 1412 cm −1 is attributed to the C–N stretching vibration of amine or amide groups [ 73 ]. The absorption bands at 1231 cm −1 and 1027 cm −1 correspond to C–O or C–O–C stretching vibrations [ 74 ]. Similar kinds of peaks were observed at 823 cm −1 , 1030 cm −1 , 1243 cm −1 , 1370 cm −1 , 1609 cm −1 , and 3347 cm −1 for biosynthesized AgNPs ( Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
“…Although, there have been numerous publications on the biosilver nanoparticles antimicrobial activity and many studies have investigated antibacterial activity of AuNPs and PtNPs, very exiguous reports are available concerning biocidal properties of trimetallic Au/Pt/Ag nanoparticles [47,48]. Yadav et al [21] have observed the synergistic antimicrobial activity of trimetallic Au/Pt/Ag nanoparticlebased nanofluid and this combination exhibited better antibacterial properties than bimetallic and single metallic nanofluid.…”
Section: Microorganismmentioning
confidence: 99%